Sunitinib-Induced Acute Interstitial Nephritis in a Thrombocytopenic Renal Cell Cancer Patient. (22nd November 2017) - Azar, Ibrahim; Esfandiarifard, Saghi; Sinai, Pedram; Wazir, Ali; Foulke, Llewellyn; Mehdi, Syed
Abstract : Sunitinib, a multitargeted tyrosine kinase inhibitor (TKI), is currently the standard of care for patients with metastatic renal cell carcinoma. Renal adverse events associated with sunitinib include proteinuria, renal insufficiency secondary to focal segmental glomerulosclerosis (FSGS), and thrombotic microangiopathy. We describe the second reported instance of biopsy-proven sunitinib-induced acute interstitial nephritis (AIN), in a challenging case complicated by thrombocytopenia. The case illustrates the importance of early diagnosis and intervention in ensuring long-term recovery from renal complications. Four other cases of AIN reported along with inhibition of the vascular endothelial growth factor (VEGF) by either TKI (sunitinib and sorafenib) or antibodies (bevacizumab) suggest a possible class effect. Given our experience, we recommend monitoring renal function with VEGF inhibition, and in the case of renal failure in the setting of an unclear diagnosis, we recommend prompt biopsy.